Field evaluation of a mobile biosafety laboratory in Senegal to strengthen rapid disease outbreak response and monitoring - Cheikh Fall; Aurélie Cappuyns; Oumar Faye; Steven Pauwels; Gamou Fall; Ndongo Dia; Moussa M. Diagne; Cheikh T. Diagne; Makhtar Niang; Alassane Mbengue; Martin Faye; Idrissa Dieng; et al. (AOSIS, 2020)
Background: Past and recent outbreaks have highlighted the vulnerability of humans to infectious diseases, which represent serious economic and health security threats. A paradigm shift in the management of sanitary crises is urgently needed. Based on lessons from the 2014 Ebola outbreak, the Praesens Foundation has developed an all-terrain mobile biosafety laboratory (MBS-Lab) for effective field diagnostics capabilities. Objective: The aim of the study was to train African teams and run a field evaluation of the MBS-Lab, including robustness, technical and operational sustainability, biosafety, connectivity, turn-around times for testing and result delivery. Methods: The MBS-Lab was deployed in Senegal in October 2017 for a six-month field assessment under various ecological conditions and was mobilised during the dengue outbreaks in 2017 and 2018. Results: The MBS-Lab can be considered an off-grid solution that addresses field challenges with regard to working conditions, mobility, deployment, environment and personnel safety. Blood (n = 398) and nasal swab (n = 113) samples were collected from 460 study participants for molecular screening for acute febrile illnesses and respiratory infections. The results showed that malaria (particularly in Kédougou) and upper respiratory tract infections remain problematic. Suspected dengue samples were tested on board during the dengue outbreaks in 2017 (882 tests; 128 confirmed cases) and 2018 (1736 tests; 202 confirmed cases). Conclusion: The MBS-Lab is an innovative solution for outbreak response, even in remote areas. The study demonstrated successful local ownership and community engagement. The MBS-Lab can also be considered an open mobile healthcare platform that offers various opportunities for field-deployable, point-of-care technologies for surveillance programmes.